The Effect of Minimum Wage and Per Capita Expenditure on Poverty in Provincial Districts D.I. Yogyakarta - Ida Bagus Putu Purbadharmaja; Luthfia Qurrotu’aini (Syntax Corporation Indonesia, 2023)
Poverty is a condition when a person lives below the poverty line and is unable to meet his basic needs. Poverty is one of the economic and social problems that is difficult to overcome. Province of D.I. Yogyakarta is the province with the highest poverty on the island of Java and ranks 11th out of 34 of the poorest provinces in Indonesia in 2021. The purpose of this study is to analyze the effect of the minimum wage and per capita expenditure on poverty in the district/cities of the province of D.I. Yogyakarta with the chosen model, namely the Random Effect Model (REM). The data used in this study are panel data for 2013-2021, the data analysis technique used is multiple linear regression with the Generalized Least Square (GLS) method with eviews 12. The results show that simultaneously the minimum wage and per capita expenditure have an effect towards poverty in the district/cities of the Province of D.I Yogyakarta. The results of the study also prove that partially the minimum wage does not have a significant effect on poverty, and per capita expenditure has a significant negative effect on poverty, which means that an increase in per capita expenditure will reduce poverty.